Critical roles of linker length in determining the chemical and self-assembly stability of SN38 homodimeric nanoprodrugs. Issue 2 (20th December 2022) - Wang, Xin; Liu, Tian; Huang, Yuetong; Dong, Fudan; Li, Lingxiao; Song, Jiaxuan; Zuo, Shiyi; Zhu, Zhengyang; Kamei, Ken-ichiro; He, Zhonggui; Sun, Bingjun; Sun, Jin
Abstract : A schematic illustration of the different linker lengths of disulfide bond-bridged SN38 homodimeric prodrug nanoassemblies for cancer therapy. Abstract : Homodimeric prodrug nanoassemblies (HDPNs) have been widely studied for efficient cancer therapy by virtue of their ultra-high drug loading and distinct nanostructure. However, the development of SN38 HDPNs is still a great challenge due to the rigid planar aromatic ring structure. Improving the structural flexibility of homodimeric prodrugs by increasing the linker length may be a potential strategy for constructing SN38 HDPNs. Herein, three SN38 homodimeric prodrugs with different linker lengths were synthesized. The number of carbon atoms from the disulfide bond to the adjacent ester bond is 1 (denoted as α-SN38-SS-SN38), 2 (β-SN38-SS-SN38), and 3 (γ-SN38-SS-SN38), respectively. Interestingly, we found that α-SN38-SS-SN38 exhibited extremely low yield and poor chemical stability. Additionally, β-SN38-SS-SN38 demonstrated suitable chemical stability but poor self-assembly stability. In comparison, γ-SN38-SS-SN38 possessed good chemical and self-assembly stability, thereby improving the tumor accumulation and antitumor efficacy of SN38. We developed the SN38 HDPNs for the first time and illustrated the underlying molecular mechanism of increasing the linker length to enhance the chemical and self-assembly stability of homodimeric prodrugs. These findings would provide new insights for the rational design of HDPNs with superior performance.